2022
DOI: 10.1186/s13568-022-01362-5
|View full text |Cite
|
Sign up to set email alerts
|

A novel recombinant chimeric bio-adhesive protein consisting of mussel foot protein 3, 5, gas vesicle protein A, and CsgA curli protein expressed in Pichia pastoris

Abstract: Despite various efforts to produce potent recombinant bio-adhesive proteins for medical purposes, efficient production of a safe and feasible bio-glue is not yet a commercial reality due to the weak properties or low expression levels. Here, a feasible expression system has been developed to produce strong recombinant fusion bioinspired protein using mussel foot protein 3 and 5 (Mfps) along with gas vesicle protein A (GvpA) of Anabaena flos-aquae, and a curli protein CsgA from E. coli, expressed under the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Moreover, the surrounding pH environment also plays an influential role in the adhesive nature of MAPs as, in a neutral or basic pH, DOPA can readily oxidize [ 33 ]. Despite these challenges, successful attempts have been made to produce functional and economical mussel-inspired protein recombinants, which mimic the adhesive characteristics of the natural MAPs found in mussels, that can be commercially produced [ 35 , 36 , 37 ]. One example of a successful attempt is a study by Bolghari and colleagues that investigated a novel combinational bio-adhesive chimeric protein that included the fusion of the gas vesicle protein A (GvpA) of Dolichospermum fosaquae , prokaryotic curli protein CsgA of Escherichia coli ( E. coli ), and DOPA-containing mussel foot proteins 3 and 5 (Mfp3, Mfp5), all expressed in methylotrophic yeast, P. pastoris [ 37 ].…”
Section: Mussel Adhesive Proteins In Dentistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the surrounding pH environment also plays an influential role in the adhesive nature of MAPs as, in a neutral or basic pH, DOPA can readily oxidize [ 33 ]. Despite these challenges, successful attempts have been made to produce functional and economical mussel-inspired protein recombinants, which mimic the adhesive characteristics of the natural MAPs found in mussels, that can be commercially produced [ 35 , 36 , 37 ]. One example of a successful attempt is a study by Bolghari and colleagues that investigated a novel combinational bio-adhesive chimeric protein that included the fusion of the gas vesicle protein A (GvpA) of Dolichospermum fosaquae , prokaryotic curli protein CsgA of Escherichia coli ( E. coli ), and DOPA-containing mussel foot proteins 3 and 5 (Mfp3, Mfp5), all expressed in methylotrophic yeast, P. pastoris [ 37 ].…”
Section: Mussel Adhesive Proteins In Dentistrymentioning
confidence: 99%
“…Despite these challenges, successful attempts have been made to produce functional and economical mussel-inspired protein recombinants, which mimic the adhesive characteristics of the natural MAPs found in mussels, that can be commercially produced [ 35 , 36 , 37 ]. One example of a successful attempt is a study by Bolghari and colleagues that investigated a novel combinational bio-adhesive chimeric protein that included the fusion of the gas vesicle protein A (GvpA) of Dolichospermum fosaquae , prokaryotic curli protein CsgA of Escherichia coli ( E. coli ), and DOPA-containing mussel foot proteins 3 and 5 (Mfp3, Mfp5), all expressed in methylotrophic yeast, P. pastoris [ 37 ]. The authors concluded that P. pastoris a suitable expression system of adhesive proteins, allowing for a higher production rate and improved post-translational modifications for the function of the protein, in addition to the greater cohesion of proteins in acidic pH 3–5.…”
Section: Mussel Adhesive Proteins In Dentistrymentioning
confidence: 99%
“…The binding and solidifying properties of MFP obtained from catechol side chain of DOPA are cross-linked with the surface of the substrate by chemical reactions. The MFP inspired the development of novel bio-based adhesives materials to fulfill the demands of satisfactory adhesive ability to wet surfaces by utilizing the advantages provided by adhesive proteins [11][12][13].…”
Section: Bio-adhesion and Bio-based Adhesivesmentioning
confidence: 99%
“…Because of the development that was carried out, a wide variety of tissue bio-based adhesives and hydrogels are now manufactured. However, their potential use as bone bio-based adhesives has been the subject of intensive research [13,47,[52][53][54][55][56].…”
Section: Sources and Types Of Bio-based Adhesivesmentioning
confidence: 99%
“…We have recently achieved recombinant fused proteinous adhesive materials consist of mussel foot proteins, MFP3, MFP5, and GvpA and CsgA in both prokaryotic ( E. coli ) and eukaryotic expression systems (Irapour et al 2021 ; Bolghari et al 2022 ). In spite of inspiring properties and obtaining chimeric structure of obtained chimeric proteins, some obstacles are still needed to be solved prior to introduce a straightforward feasible approach for their industrial production.…”
Section: Introductionmentioning
confidence: 99%